The way of the brave [large type] - Warren, Susan May, 1966- (Warren, Susan May, 1966- Global search and rescue., 2020)
"Jenny Calhoun climbs mountains to forget what she's done, who she was. But this time, when an excursion up Denali turns deadly, she is forced to accept the help of the one man she hoped she'd never see again--the man she nearly killed"--Provided by publisher.